East of Eden - Steinbeck, John, 1902-1968. (New York : Viking Press, 1962)
The saga of an American family, from the Civil War to World War I and from a Connecticut farm to a valley in California.
Keywords: Fathers and sons -- California -- Salinas River Valley -- Fiction; Salinas River Valley (Calif.) -- Fiction; Domestic fiction; Large type books; Western stories